Kedudukan Daerah Khusus Ibu Kota Jakarta Pasca Pemindahan Ibu Kota Negara dalam Perspektif UU Nomor 3 Tahun 2022 tentang IKN dan Perubahannya serta UU Daerah Khusus Jakarta - Siti Rifqa Raihani; Syah Ramadhan Putra; Wicipto Setiadi (Lembaga Yasin AlSys, 2026)
Although the strategic policy of relocating the national capital from Jakarta to Nusantara has been established, its implementation continues to generate legal complexity, particularly regarding the dualism of capital status between factual governmental functions and formal juridical legality that has not yet been fully resolved. This legal uncertainty is reflected in the unclear timing of the termination of Jakarta’s status as the national seat of government, given that the activities of high state institutions are still taking place in the area even though Undang-Undang Nomor 2 Tahun 2024 tentang Provinsi Daerah Khusus Jakarta has been promulgated. This study aims to analyze the status of Jakarta following the relocation of the national capital from the perspective of Undang-Undang Nomor 3 Tahun 2022 and Undang-Undang Nomor 2 Tahun 2024. This study employed a normative juridical method with a statutory approach and a conceptual approach. The results show that the synchronization between Undang-Undang Nomor 3 Tahun 2022 and Undang-Undang Nomor 2 Tahun 2024 positions a Presidential Decree as an essential instrument and the main determining variable in the transition of capital status in order to maintain the stability of the state administrative system and prevent a legal vacuum. In addition, Jakarta is projected to experience a shift in role as Pusat Perekonomian Nasional and Kota Global as stipulated in Article 3 paragraph (2) of Undang-Undang Nomor 2 Tahun 2024, supported by special functional-economic authority, including in the sectors of international investment and integrated strategic infrastructure development. These findings contribute to strengthening constitutional law studies, particularly regarding regulatory synchronization and legal certainty in the process of institutional transition of the state. This study affirms that the clarity of the legal instrument of transition is an important factor in determining the end of Jakarta’s status as the national capital while at the same time restructuring its role as a global city that supports national economic growth.